Performance in Neurocognitive Tasks in Obese Patients. Does Somatic Comorbidity Matter? - Kiunke, Wibke; Brandl, Christina; Georgiadou, Ekaterini; Gruner-Labitzke, Kerstin; Horbach, Thomas; Köhler, Hinrich; de Zwaan, Martina; Müller, Astrid (Frontiers in Psychiatry, 2013)
The aim of the present study was to examine if obese individuals with obesity-related somatic comorbidity (i.e., hypertension, diabetes, sleep apnea, dyslipidemia, pain disorder) perform worse in neurocognitive tasks compared to obese individuals without any somatic disorder. Neurocognitive functioning was measured by a computerized test battery that consisted of the following tasks: Corsi Block Tapping Test, Auditory Word Learning Task, Trail Making Test-Part B, Stroop Test, Labyrinth Test, and a 4-disk version of the Tower of Hanoi. The total sample consisted of 146 patients, the majority (N=113) suffered from obesity grade 3, 26 individuals had obesity grade 2, and only 7 individuals obesity grade 1. Ninety-eight participants (67.1%) reported at least one somatic disorder (Soma+-group). Hypertension was present in 75 individuals (51.4%), type 2 diabetes in 34 participants (23.3%), 38 individuals had sleep apnea (26.0%), 16 suffered from dyslipidemia (11.0%), and 14 individuals reported having a chronic pain disorder (9.6%). Participants without a coexisting somatic disorder were younger (MSoma-=33.7, SD=9.8 vs. MSoma+=42.7, SD=11.0, F(1,144)=23.01, p<0.001) and more often female (89.6% and 62.2%, χ2(1)= 11.751, p=0.001) but did not differ with respect to education, regular binge eating or depressive symptoms from those in the Soma+-group. The Soma--group performed better on cognitive tasks related to memory and mental flexibility. However, the group differences disappeared completely after controlling for age. The findings indicate that in some obese patients increasing age may not only be accompanied by an increase of obesity severity and by more obesity-related somatic disorders but also by poorer cognitive functioning.